SURVEY OF POLLINATORS ON SOME VEGETATION COVER AT AHMADU BELLO UNIVERSITY, SAMARU, ZARIA - Uyovbisere , E. E; Abubakar , B.Y (UNILAG Journal of Medicine, Science and Technology, 2020)
Decline in biodiversity and population of pollinators have similar declining effect on the corresponding pollinated plant species, therefore efforts at conservation, perpetuation and establishment of the pollinators are necessary. Hence the survey of pollinators of some selected vegetation cover within Global Positioning System coordinates of 11̊ 09̍̍ 30̎ N, 007 ̊ 38̍ 0̎ E & 11̊ 10̍ 00̎ N, 007̊ 38̍ 30̎ E, at Area F, Ahmadu Bello University, Staff Quarters, Zaria. The vegetation was luxuriant, diverse and comprised more than nine species of flowering plants. In a six months’ survey, aimed at conservation of the pollinators and conducted at four days interval between 6:00am and 8:00am or 16:00 and 18:00pm GMT, from January to June, 2016. The flowering plants and their pollinator visitors were identified, the dangers and threats, and the advantages and opportunities for the pollinators were determined. More than twenty-seven species within seven insect orders and two bird species of the Order Passeriformes were the observed pollinator visitors. Birds and insects made up 6.37% and 85.39% respectively of the pollinators while bees alone constituted 31% of the bulk of 91.76% of observed pollinators. The flowering plants provided rewards as nutrients, habitats and breeding sites for the animal pollinators. Loss of habitat and fragmentation due to agricultural activities and construction were among the dangers and threats to the pollinators.